Perlakuan Benih dengan Agen Hayati dan Pemupukan P untuk Meningkatkan Pertumbuhan Tanaman, Hasil, dan Mutu Benih Padi - Agustiansyah, ,; Ilyas, Satriyas; Sudarsono, ,; Machmud, Muhammad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
The objective of the study was to determine the effect of seed treatment on growth, seed quality, P fertilizer utilization, and rice production in the glasshouse. The experiment was conducted in a split plot design with three replications from January to June 2010.The main plots were P fertilizer rates (0, 50, and 100 kg SP-36 ha-1), and sub plots were (1) negative control (seeds were not inoculated by Xanthomonas oryzaepv. oryzae(Xoo) and without seed treatment); (2) positive control (seeds were inoculated by Xoo); (3) seeds were inoculated by Xoo and immersed in Pseudomonas diminutaA6 suspension; (4) seeds were inoculated by Xoo and immersed in Bacillus subtilis5/B suspension; (5) seeds were inoculated by Xoo and immersed in P. diminutaA6 + B. subtilis5/B suspension; (6) matriconditioning + P. diminutaA6, (7) matriconditioning + B. subtilis5/B, and (8) matriconditioning + P. diminutaA6 + B. subtilis5/B. The results showed that seed treatment with biological agents P. diminutaA6, seed treatment with P. diminutaA6 + B. subtilis5/B were the best seed treatments to improve plant growth and yield of rice. Treatment with matriconditioning + P. diminutaA6 + B. subtilis5/B was the best treatment to enhance seed germination. Soaking the seeds in B. subtilis5/B suspension or P. diminutaA6 + B. subtilis5/B suspension reduced the use of P fertilizer, based on the number of grain, total number of grain, percentage of grain per panicle. The highest seed yield obtained from both treatments was with the application of P fertilizer 50 kg ha-1. Keywords: biopriming, matriconditioning, rhizobacteria, seed viability, seed vigorABSTRAK